2021
DOI: 10.1038/s41598-021-90367-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative nomogram of intratumoral, peritumoral, and lymph node radiomic features for prediction of lymph node metastasis in cT1N0M0 lung adenocarcinomas

Abstract: Radiomics studies to predict lymph node (LN) metastasis has only focused on either primary tumor or LN alone. However, combining radiomics features from multiple sources may reflect multiple characteristic of the lesion thereby increasing the discriminative performance of the radiomic model. Therefore, the present study intends to evaluate the efficiency of integrative nomogram, created by combining clinical parameters and radiomics features extracted from gross tumor volume (GTV), peritumoral volume (PTV) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 57 publications
(96 reference statements)
0
22
0
Order By: Relevance
“…We also found that the high-dimensional features of multiple radiological features could be integrated to further reduce the workload of identification by radiologists. In addition, we compared the results with other studies (32)(33)(34), and the results showed that the evaluation effect of our nomogram was more accurate and robust in the verification set (Table S2).…”
Section: Discussionmentioning
confidence: 98%
“…We also found that the high-dimensional features of multiple radiological features could be integrated to further reduce the workload of identification by radiologists. In addition, we compared the results with other studies (32)(33)(34), and the results showed that the evaluation effect of our nomogram was more accurate and robust in the verification set (Table S2).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that model-based schemes can make better utilize radiographic information to predict lymph node diseases [31]. Das et al integrated clinical parameters and radiomics features extracted from three ROIs of gross tumor volume (GTV), peritumoral volume (PTV), and LN in different ways to create different nomograms for predicting preoperative LNM in adenocarcinoma, and compared the predictive e ciency of each model [32]. The results showed that the AUC of radiological features based on GTV, PTV and LN in the external veri cation cohort were 0.74,0.72 and 0.64 respectively; the AUC of integrating GTV and PTV (GPTV) was 0.75 in the external validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…developed a model to predict the lymph node status of cT1N0M0 lung adenocarcinoma, either alone or in combination with clinical features. The external validation group yielded an AUC of 0.79 (95% CI, 0.66–0.93) ( 32 ). In our study, the combined GTV+CTV model based on traditional CT imaging also exhibited a comparable predictive ability with an AUC value of 0.845.…”
Section: Discussionmentioning
confidence: 99%